Mechanical properties, thermal stability and microstructure of fine-grained W-0.5 wt.% TaC alloys fabricated by an optimized multi-step process. (December 2017) - Miao, S.; Xie, Z.M.; Zeng, L.F.; Zhang, T.; Wang, X.P.; Fang, Q.F.; Liu, C.S.
Highlights: Fine-grained W-0.5 wt.% TaC alloys are fabricated by a multi-step process. W-0.5 wt.% TaC alloys show high strength and ductility at 200 °C. The uniform distribution of TaC in grains improves the mechanical properties. Abstract: Tungsten materials with high ductility/strength are highly desirable for a wide range of critical applications. Fine-grained W-0.5 wt.% TaC alloys were produced by an optimized multi-step process, consisting of high-energy ball milling, hot press sintering and subsequent hot rolling. Grain refinement induced improvement in mechanical properties is achieved with ultimate tensile strength (UTS) of 982 MPa and total elongation (TE) as large as ∼12.0% at 200 °C. UTS values are over 570 MPa at all tested temperature ranging from RT to 500 °C and the TE increases to ∼40.5% at 400 °C. These good mechanical properties are attributed to advanced process routes. Hydrogen atmosphere during the fabrication reduces oxygen impurity contents and then decreases the amount of submicron oxide particles. The multi-step process routes generate optimal microstructures with nanometric TaC particles uniformly distributed in the submicron subgrains interior. Nano-sized particles could hinder grain boundary migration, reduce grain growth rate and thus keep microstructure stability, improving low-temperature strength and ductility of W-TaC alloys. The optimized fabrication routes for such refractory alloys offer a general pathway for manufacturing bulk dispersion-strengthened materials with both good mechanical properties and thermal stability.